Geometry of nonholonomic complexes NGr (1, 5, 5) - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2011)
In this article the differential geometry of nonholonomic complexes in five dimensional projective space is considered. The algebraic structure of the first fundamental object is considered and the geometrcal interpretations of some comitants of the first fundamental object are given.